Severe ornithine transcarbamylase deficiency. Two and a half years' survival with normal development. Issue 5 (May 1984) - Guibaud, P; Baxter, P; Bourgeois, J; Louis, J J; Bureau, J
Abstract : The clinical course and management of a boy with severe ornithine transcarbamylase deficiency are described. In addition to treatment with sodium benzoate and amino acid keto analogues, mannitol may be useful in hyperammonaemia and nocturnal gavage feeding aids maintenance treatment.